PELATIHAN MEMBAWAKAN ACARA DAN BERPIDATO PADA APARAT PEKON WAYAKRUI BANYUMAS PRINGSEWU - Lisdwiana Kurniati; Izhar Izhar; Sholikhin Sholikhin (Bagimu Negeri, 2017)
Many staff of Wayakrui Banyumas, Pringsewu could not deliver agenda and speech well. In delivering agenda, they got difficulties in selecting effective sentence, intonation, and performing agende in front of the audience. Moreover the problem occured in speech are speech ability sistematically, sentence use, and the ability in developing speech content. This dedication aims to assist village staff in order to be able in delivering agenda and speech well. The method used in this services are (1) preparing: observing  activity in the location, discussing with the village staff, preparing training material, and facility; (2) action: delivering material about master of ceremony and speech, then practicing both of them; (3) evaluation: giving feed back of training acitivty. The service result shows that 80% of staff in Wayakrui Banyumas are motivated and they are able to deliver agende and speech well. Keywords: Speech, Master of Ceremony